IMPLICATIONS OF KNOWLEDGE SOCIETY ON THE SUSTAINABLE DEVELOPMENT: THE SINGAPORE EXPERIENCE - Ahmed Ibrahim Mahdi Alzurfi, Ali Ismael Abd al Mageed, Hind Ghanim Mohammad al mohan, Abaas Asfore Lafta, Abbas Makki Hamzah (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
It is an economic axiom that the economy cannot function and achieve sustainable growth without drawing up long-term and short-term economic policies and strategies that have known goals. The other axiom: It is not possible for an economy to function in isolation from the economic and social developments that were drawn by the features of the information revolution that globalization and its givens have produced. From the foregoing, the topic of study directly overlaps with those axioms, so it discusses the topic of sustainable development and the role of the knowledge society in fulfilling its requirements by adopting a pioneering experience in this dualism, which is the Singapore experience, its advantages and basic pillars for success. Thus, how can the Iraqi economy benefit from this experience in changing its social and economic reality, which has suffered for decades from ineffective developmental experiences in finding appropriate solutions to advance human capabilities and have multiple options for participation in the production process? In light of this, the research aims to explain the role of the knowledge society in the sustainable growth of the Singaporean economy based on sustainable development strategies that were followed by the planners and implementers of the general economic policies of the country. It also aims to uncover the most important challenges and obstacles facing the Iraqi economy in building its knowledge capabilities and what is the capacity of all classes of society in the process of using it as a means of unconventional production and simulating the sustainable development experience in Singapore. The final goal is how the economic philosophy of the Iraqi state can contribute to its adoption of a sustainable development approach based on the knowledge society